“It is necessary for women to be self-conscious.” An analysis of the rationalist ideology on women from the Boletín de la Escuela Moderna (1901-1909) - Fernández Antón, Estefanía; Sonlleva Velasco, Miriam (Cuadernos de Historia, 2024)
The aim of the article is: to analyze her discourse about women in the Boletín de la Escuela Moderna. To do this, the issues published between 1901 and 1909 are examined. These are kept at the Fundación Ferrer i Guàrdia and at the Historical Archive of Barcelona (Spain). The documentary analysis reveals that the rationalist discourse includes two spheres: public and private. Within the private space, women’s freedom is conditioned by marriage and maternity. Rationalism seeks female emancipation through the free union between the sexes. Likewise, it is committed to a conscious, voluntary maternity and protected by public powers. In the public sphere, rationalist education and salaried work are key to the social liberation of women. However, the discourse proves ineffective in enabling women to break free from their biological and social destiny.